Sensing of protease activity as a triggering mechanism of Th2 cell immunity and allergic disease - Meloun, Audrey; León, Beatriz (Frontiers in Allergy, 2023)
CD4 T-helper cell type 2 (Th2) cells mediate host defense against extracellular parasites, like helminths. However, Th2 cells also play a pivotal role in the onset and progression of allergic inflammatory diseases such as atopic dermatitis, allergic rhinitis, asthma, and food allergy. This happens when allergens, which are otherwise harmless foreign proteins, are mistakenly identified as "pathogenic." Consequently, the encounter with these allergens triggers the activation of specific Th2 cell responses, leading to the development of allergic reactions. Understanding the molecular basis of allergen sensing is vital for comprehending how Th2 cell responses are erroneously initiated in individuals with allergies. The presence of protease activity in allergens, such as house dust mites (HDM), pollen, fungi, or cockroaches, has been found to play a significant role in triggering robust Th2 cell responses. In this review, we aim to examine the significance of protease activity sensing in foreign proteins for the initiation of Th2 cell responses, highlighting how evolving a host protease sensor may contribute to detect invading helminth parasites, but conversely can also trigger unwanted reactions to protease allergens. In this context, we will explore the recognition receptors activated by proteolytic enzymes present in major allergens and their contribution to Th2-mediated allergic responses. Furthermore, we will discuss the coordinated efforts of sensory neurons and epithelial cells in detecting protease allergens, the subsequent activation of intermediary cells, including mast cells and type 2 innate lymphoid cells (ILC2s), and the ultimate integration of all signals by conventional dendritic cells (cDCs), leading to the induction of Th2 cell responses. On the other hand, the review highlights the role of monocytes in the context of protease allergen exposure and their interaction with cDCs to mitigate undesirable Th2 cell reactions. This review aims to provide insights into the innate functions and cell communications triggered by protease allergens, which can contribute to the initiation of detrimental Th2 cell responses, but also promote mechanisms to effectively suppress their development.